KNOWLEDGEABLE UNDERSTANDING ANALYSIS AND THE BENEFITS OF HOUSEHOLD ACCOUNTS FOR THE HMONG TRIBE AT HUAY HAN VILLAGE, WIANGKAEN DISTRICT, CHIANG RAI PROVINCE - Putsom, Subin; Putsom, Wanlee; Koonkhuntod, Shadathip; Yodmaneebunpot, Sopida (11th International Scholars Conference, 2016)
This survey research aims to 1) examine the demographic characteristics, knowledgeable understanding, problems and barriers, and the benefits of household account preparation, 2) study the knowledgeable understanding level and the benefit of household accounts by age and income, and 3) study the difference between the knowledgeable understanding and the benefit of household accounts. The samples were the Hmong of about 202 households at Huay Han village, Wiangkaen district, Chiang Rai province and survey questionnaires were distributed. The statistical analysis performed was frequency, percentage, average, standard deviation, F-test and statistical MANOVA. The results showed that most of the respondents were male at the age of 31 – 40 years old. The average monthly income was 5,000 baht to 10,000 baht. The knowledgeable understanding level for household accounts and the highest benefits of household account by the ages and income was medium level. The statistical test was done in accordance with the initial conditions of MANOVA, variables tested by Wilk’s Lambda statistic was statistical significant at the 0.05 level. The test result demonstrated no significant difference in pairs among age groups regarding knowledgeable understanding in household accounts and its benefits. However, there were significant differences in pairs among different monthly incomes regarding knowledgeable understanding in household account and its benefits at statistical level of 0.05.